2016
DOI: 10.5999/aps.2016.43.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Temporal Augmentation Using a Calvarial Onlay Graft during Pterional Craniotomy

Abstract: Temporal hollowing occurs to varying degrees after pterional craniotomy. The most common cause of temporal hollowing is a bony defect of the pterional and temporal regions due to the resection of the sphenoid ridge and temporal squama for adequate exposure without overhang. The augmentation of such bony defects is important in preventing craniofacial deformities and postoperative hollowness. Temporal cranioplasty has been performed using a range of materials, such as acrylics, porous polyethylene, bone cement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Unlike the previous method using one big bone flap, we used two separate bone segments (which was divided from the large bone flap) to cover bony defect and to augment the temporal area. In addition, the current study included 100 patients to improve the reliability of the study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the previous method using one big bone flap, we used two separate bone segments (which was divided from the large bone flap) to cover bony defect and to augment the temporal area. In addition, the current study included 100 patients to improve the reliability of the study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The senior author had previously presented a primary temporal reconstruction technique using one autologous bone graft for coverage of temporal defect and temporal area [ 6 ]. This technique successfully prevented temporal hollowing, but the bony plate positioning was limited due to its large size.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapeutic methods have been developed for reconstruction of temporal hollowing using both autograft and alloplast materials. Autologous bone has the advantages of being genetically identical to the patient, possessing the potential for growth and replacement of host cells, and a low incidence of infection [ 16 , 28 32 ]. However, it causes donor site morbidity, graft resorption, and difficulties with contouring, and additional time is required for harvesting of the graft [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have argued that the most common cause of temporal hollowing is bony defect of the pterional and temporal regions due to the resection of the sphenoid ridge and temporal squama for adequate exposure. 17 However, no data have yet been produced to support this hypothesis. Our study showed that the average bony volume reduction was 9.10 cm 3 (3.99%).…”
Section: Figmentioning
confidence: 99%
“…Both immediate and late reconstructions of the temporal area have been reported, with many materials, including autogenous and nonbiologic materials, used. 14,[17][18][19][20][21][22][23][24] No definitive implants have demonstrably yielded the best results.…”
Section: Figmentioning
confidence: 99%